Comparative Analysis of Rabies Virus Reverse Transcription-PCR and Virus Isolation Using Samples from a Patient Infected with Rabies Virus - Panning, Marcus (American Society for Microbiology (ASM), 2010)
Definite and rapid diagnosis of rabies is required for individual case management as well as for public health. For the first time, a direct comparison of virus isolation with quantitative real-time reverse transcription (RT)-PCR on human rabies samples was conducted. RT-PCR was found to be more sensitive than virus isolation.